From the Public Space to the Prison Space: Regulation Polemic and the Implementation of Caning Law in Aceh - Mizaj Iskandar; Azhari Yahya; Abdul Jalil Salam; Junaidi (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
The implementation of caning law in Aceh Province is still sporadic due to a lack of coordination among the government institutions involved in caning law. Then, the prison infrastructure to impose the canning law is also not ade-quate, and socialization has also not been fully carried out. Besides, in deter-mining the location of the caning, Islamic law requires the fulfillment of two principles namely “open space” and “visible” to the public. Furthermore, the law that guides the implementation of sharia in Aceh does not regulate detail of where the caning can be executed. Hence, the issues that need to be scruti-nized in this study are about shifting the norm from “open space" to “prison space” and why there is a disparity in determining the place of caning sentenc-es. This study uses a normative legal method by relying on secondary data. All collected data were analyzed by using qualitative analysis. The results show that there has been a shifting norm from "open space" to “prison space” in the application of the caning sentences in Aceh. This shift starts from the open area in the courtyard of the mosque to the prison area as a place to execute a caning sentence. This shifting also allows the people who meet certain criteria to wit-ness the execution of a caning sentence. In addition, there is also a disparity among the sharia courts due to the lack of facilities available in certain the sha-ria courts in Aceh. Hence, the Aceh government needs to improve the facilities of the sharia courts to be able to execute caning sentences.